Low energy spent coffee grounds briquetting with organic binders for biomass fuel manufacturing. (15th October 2020) - Espuelas, S.; Marcelino, S.; Echeverría, A.M.; del Castillo, J.M.; Seco, A.
Highlights: Pure spent coffee grounds were not able to produce functional briquettes. Xanthan and guar gums produced good mechanical properties briquettes. Xanthan and guar gums required high moisture contents to be effective. 5% of xanthan gum and 30% of moisture produced the best briquettes. Xanthan and guar gums modified spent coffee grounds combustion characteristics. Abstract: This paper analyzes the ability of the spent coffee grounds (SCG) for briquettes production with xanthan and guar gums as binders. Briquettes were manufactured at room temperature, at 15%, 20%, 25% and 30% of moisture, at 8 MPa, 10 MPa and 12 MPa of compaction pressure and at 5 and 10% of binder dosage. Combination of 10% of xanthan, 15% of moisture, at 12 MPa, reached the highest dry density, 0.819 g/cm 3 . The combination of 5% of xanthan, 30% of moisture, compacted at 12 MPa was the most durable with a loss of mass of 3.9%. No relationships were established among water absorption and binder type, binder dosage, manufacturing moisture or compaction pressure. The lowest water absorption value, 0.25%, corresponded to the combination with 5% of xanthan, 30% of moisture, compacted at 10 MPa. The lowest heating value achieved by SCG was 25, 399 J/g. Guar 5% and 10% combinations achieved 24, 398 J/g and 24, 321 J/g respectively. Xanthan gum 5% and 10% dosages attained 24, 450 and 23, 503 J/g. Binder decreased volatiles, increased fixed carbon content and decreased nitrogen content. Guar gum decreased SCG nitrogen content by 15.92% for the 5% and by 16.92% for the 10% dosage combinations, respectively. Xanthan nitrogen reduction attained 13.43% for the 5% and 14.43% for the 10% of dosage. The raw SCG ash production was 0.66%. This value increased to 0.81% and 0.97% with 5% and 10% of xanthan gum, meanwhile guar decreased it to 0.57% and 0.52%, at 5% and 10% of dosage.